Characterization of a NIR absorbing thienyl curcumin contrast agent for photoacoustic imaging. Issue 49 (5th June 2018) - Bellinger, Stephanie; Hatamimoslehabadi, Maryam; Borg, Raymond E.; La, Jeffrey; Catsoulis, Peter; Mithila, Farha; Yelleswarapu, Chandra; Rochford, Jonathan
Abstract : Photophysical and photoacoustic characterization of the bis-(2-dimethylaminothien-5-yl)curcumin boron difluoride chromophore is presented. Abstract : The synthesis and characterization of a bis(2-dimethylaminothien-5-yl)curcumin boron difluoride chromophore is presented. Photophysical, electrochemical and computational investigations establish the properties of its absorption in the Vis-NIR spectral range relative to established curcumin dyes. Application of this thienyl curcumin dye as a photoacoustic contrast agent is investigated against the dicarbocyanine Cy5 dye in the 675–735 nm excitation range.